Personality education: Between external deteminism and freedom - Vilotijević, Nada M.; Mitić, Ljiljana B.; Vilotijević, Goran M. (Sociološki pregled, 2018)
This paper discusses the understanding of personality from social, psychological and philosophical aspects. It is emphasized that a person is a unity of unique and universal properties and has the right to freely develop his/her potential and live in accordance with the needs of his/her spirit. Tere are some contradictions between personal needs and interests of society. Education is an area that should help every individual to express his/her unique individuality. Education, however, acts between the two poles - free decision making, on the one hand, and social (state) coercion, on the other. Externally imposed determinism and the instrumentalist-market approach to education signifcantly restrict freedom of an individual to self-develop in accordance with his/her needs.